Survey of Linyphiidae spiders (Arachnida: Araneae) from Wulipo National Nature Reserve, Chongqing, China - Irfan, Muhammad; Wang, Lu-Yu; Zhang, Zhi-Sheng (European Journal of Taxonomy, 2023)
An extensive survey of Linyphiidae spiders from Wulipo National Nature Reserve (NNR), Chongqing has been conducted, in which 24 species belonging to 16 genera are recorded including two new genera and eight new species described here as: Agyneta Hull, 1911, A. orthogonia sp. nov. (♂♀); Dicristatus gen. nov., D. minutus gen. et sp. nov. (♂♀); Dicymbium Menge, 1868, D. pingqianense sp. nov. (♂♀); Himalaphantes Tanasevitch, 1992, H. azumiensis (Oi, 1979) (♂♀); Indophantes Saaristo & Tanasevitch, 2003, I. wushanensis sp. nov. (♂♀); Ketambea Millidge & Russell-Smith, 1992, K. nigripectoris (Oi, 1960) (♂♀); Molestia Tu, Saaristo & Li, 2006, M. pollicaris sp. nov. (♂♀); Neriene Blackwall, 1833, N. calozonata Chen & Zhu, 1989 (♀), N. cavaleriei (Schenkel, 1963) (♂♀), N. emphana (Walckenaer, 1841) (♂♀), N. japonica (Oi, 1960) (♂♀), N. limbatinella (Bösenberg & Strand, 1906) (♀), N. longipedella (Bösenberg & Strand, 1906) (♂♀), N. oidedicata van Helsdingen, 1969 (♀); Prosoponoides Millidge & Russell-Smith, 1992, P. sinense (Chen, 1991) (♂♀); Ryojius Saito & Ono, 2001, R. simplex sp. nov. (♂♀); Stemonyphantes Menge, 1866, S. bifurcus sp. nov. (♂); Syedra Simon, 1884, S. oii Saito, 1983; Tapinopa Westring, 1851, T. guttata Komatsu, 1937 (♀); Tenuiphantes Saaristo & Tanasevitch, 1996, T. ancatus (Zhu, Li & Sha, 1986) (♂♀); Walckenaeria Blackwall, 1833, Walckenaeria asymmetrica Song & Li, 2011 (♂♀); Wuliphantes gen. nov., W. guanshan (Irfan, Wang & Zhang, 2022) gen. et comb. nov. (♂♀), W. tongluensis (Chen & Song, 1988) gen. et comb. nov. (♂♀), W. trigyrus gen. et sp. nov. (♂♀). Male of Tenuiphantes ancatus (Zhu, Li & Sha, 1986) is described here for the first time as new to science. The taxonomic status of Bathyphantes guanshan Irfan, Wang & Zhang, 2022 and Bathyphantes tongluensis (Chen & Song, 1988) is revised and proposed here as: Wuliphantes tongluensis (Chen& Song, 1988) gen. et comb. nov. (♂♀) and Wuliphantes guanshan (Irfan, Wang & Zhang, 2022) gen. et comb. nov. (♂♀), respectively. Morphological descriptions, photos of body and copulatory organs, as well as the locality map are provided.